CZYH Alleviates β-Amyloid-Induced Cognitive Impairment and Inflammation Response via Modulation of JNK and NF-κB Pathway in Rats. (4th November 2019) - Deng, Yuanyuan; Ye, Lianzhi; Yu, Cheng; Yin, Caixia; Shi, Jingshan; Gong, Qihai
Abstract : Cu-Zhi-Yi-Hao (CZYH), an empirical formula of traditional Chinese medicine (TCM), has been used for amnesia treatment in clinical practice. However, its underlying pharmacological mechanism has not been fully illuminated. The current study was designed to investigate the neuroprotective effect of CZYH on a β -amyloid 25-35- (A β 25-35 -) induced learning and memory deficit rat model. CZYH (200, 400, or 800 mg/kg), donepezil (1.0 mg/kg), or distilled water was given to A β 25-35 -stimulated animals for 17 days consecutively. The Morris water maze test revealed that CZYH (400 or 800 mg/kg) administration improved the A β 25-35 -induced cognitive impairments in rats, and Nissl staining demonstrated that CZYH mitigated the A β -caused neuron loss. In addition, CZYH treatment markedly inhibited the activation of microglia as evidenced by a decreased level of IBA-1 and increased YM-1/2 protein expression. The protein expression levels of TNF- α, IL-1 β, and COX-2 were also repressed by CZYH. Besides, CZYH treatment alleviated A β -induced I κ B- α degradation and NF- κ B p65 phosphorylation, as well as reduced the JNK phosphorylation level. In conclusion, the present study suggests that CZYH could improve learning and memory abilities and relieve neuron loss in A β 25-35 -induced rats, at least partly through inhibition of the neuroinflammatory response via inhibiting the JNK-dependent NF- κ B activation, indicating that CZYH might be a promising formula for the treatment of AD.